The valuation effects of trade - Omar Barbiero (Federal Reserve Bank of Boston, 2021)
This paper estimates the cash flow and real effects of currency mismatches generated by foreign-priced operations of French manufacturers. The value of transactions invoiced in foreign currencies is twice as sensitive to exchange rates as the value of transactions invoiced in the domestic currency. I aggregate foreign-priced operations to the firm level to build a shift-share measure of invoice currency mismatch. This measure outperforms any trade-weighted effective exchange rate index in explaining cash flows of trading firms. Large firms absorb valuation shocks in their balance sheet, and small exporters partially hedge their dollar-priced exports with dollar-priced imports. Only investment and payroll of small domestic-oriented firms are sensitive to invoice currency valuations. These results show how trade value sensitivities to currency fluctuations can coexist with the evidence of disconnect between exchange rates and real macroeconomic fundamentals.
Keywords: F30; F31; F32; F34; F36; F40; F41; F42; 330; exchange rate sensitivity; currency mismatch; dollar-priced trade